2D beam dynamics simulation in linear mode LPWA channel with pre-modulation stage - Polozov, S.M. (Вопросы атомной науки и техники, 2013)
Laser plasma wakefield acceleration (LPWA) is one of most popular novel methods of acceleration. The acceleration process differs significantly for linear LPWA mode and bubble (non-linear) modes. The LPWA has two serous disadvantages as very high energy spread and low part of electrons trapped into acceleration. The energy spectrum better than 10% does not observed anyone in simulations or experiments without of especial plasma density distribution. Such simulations and first experiments was done for bubble mode with different injection methods as varying of plasma density into bunching sub-stage, pondermotive injection, etc. But linear mode LPWA is also very interesting to design a compact hundreds-MeV accelerator. 2D beam dynamics in linear mode LPWA is discussed in this report. The waveguide and klystron type beam pre-modulation schemes are studied. The simulation shows that the klystron type pre-modulation can to gives the energy spectrum better than 1.5% for 200…300 MeV beam and to achieve the capturing coefficient 70…80%.